2011
DOI: 10.1590/s0104-07072011000100016
|View full text |Cite
|
Sign up to set email alerts
|

Cumprimento da terapia com antidiabéticos orais em usuários da atenção primária

Abstract: EL CUMPLIMIENTO DEL TRATAMIENTO CON ANTIDIABÉTICOS ORALES EN USUARIOS DE LA ATENCIÓN BÁSICARESUMEN: El objetivo de este estudio fue evaluar el cumplimiento del tratamiento farmacológico por los usuarios de antidiabéticos orales. En la investigación participaron 437 pacientes diabéticos de ambos sexos, con edades entre 18 a 92 años, de 12 unidades básicas de salud de la ciudad de Fortaleza -Ceará, Brasil, de marzo a junio de 2009. Con el fin de evaluar la adhesión a los antidiabéticos orales se aplicaron en los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 15 publications
0
9
0
21
Order By: Relevance
“…Cross-sectional studies involving DM patients in PHC reported rates between 13.7 and 84.4% [30][31][32] , depending on the method used to measure adherence. It is possible to observe the great variation between the rates found in the literature, probably due to the methods applied and interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cross-sectional studies involving DM patients in PHC reported rates between 13.7 and 84.4% [30][31][32] , depending on the method used to measure adherence. It is possible to observe the great variation between the rates found in the literature, probably due to the methods applied and interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Access was defined as the acquisition of medicines prescribed for DM and classified into three categories: total (when the respondent had access to all drugs prescribed for DM within 30 days prior to the interview); partial (if respondent lacked any medication in the period); or null (if no prescribed medication was obtained in the period, due to lack of user resources or lack of supply in the SUS unit) 32,33 . The method of purchasing was also classified into three categories: free (when the respondent did not pay for any DM medication); mixed (at least one of the medicines was purchased out of the respondent's own resources); or out of their own resources (when respondents paid for all medicines in use) 32,33 .…”
Section: Study Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Atualmente, o tratamento para manter a normoglicemia é a adoção de dieta hipocalórica, aumento da prática de exercícios físicos e uso de medicações (quando necessário), pois diminuindo a ingestão de alimentos calóricos já se reduz três dos fatores de risco para doença cardiovascular, que são a obesidade, a dislipidemia e a hipertensão arterial. 16,22,23 Houve certa linealidade na distribuição de pessoas que realizaram o exame de glicemia de jejum durante o ano. Mas, nos meses de maio e outubro, houve uma parcela maior de indivíduos, sugerindo que as variações térmicas podem ter influenciado, aumentando a procura das pessoas, tanto para atendimento médico, como para realização de exames.…”
Section: Tipo De Atendimento Perfil Epidemiológico De Pacientes Portaunclassified